2017
DOI: 10.1080/09581596.2017.1329520
|View full text |Cite
|
Sign up to set email alerts
|

Public engagement and the role of the media in post-marketing drug safety: the case of Eltroxin® (levothyroxine) in New Zealand

Abstract: The potential for harms from adverse drug reactions (ADR) constitutes wawcritical patient safety and public health challenge, especially with increased medication usage as populations age. The research reported here explores explanations for a sudden increase in ADR reporting in New Zealand after a new formulation of a medication to treat hypothyroidism, Eltroxin ® (levothyroxine), was phased in. The formulation was adjudged to be bioequivalent to the old formulation, yet following its introduction, a sharp in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Great care must be taken to keep clinicians and patients fully informed when a reformulated branded product is introduced, and pharmacovigilance plans should be in place to monitor adverse events [21, 24, 81].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Great care must be taken to keep clinicians and patients fully informed when a reformulated branded product is introduced, and pharmacovigilance plans should be in place to monitor adverse events [21, 24, 81].…”
Section: Discussionmentioning
confidence: 99%
“…Similar problems occurred in New Zealand and Denmark a decade ago in relation to reformulated Eltroxin [21, 43, 74, 81]. A major review of the New Zealand situation also found no clear reason for the level of reported adverse events with reformulated Eltroxin [82].…”
Section: Problems Encountered After Forced Switching On a National Levelmentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, the creation of online pharmacovigilance reporting tools, such as the 'Portail de signalement des ev enements sanitaires ind esirables' in France in 2017, may facilitate ADRs reporting by patients themselves [20]. Those tools have already proven their value with the report of neglected and/or unknown ADRs by clinicians [21].…”
Section: Discussionmentioning
confidence: 99%
“…The opt-out default resulted in the overall generic prescribing rate to increase (in 7 months post-intervention) significantly for all drugs except levothyroxine. The opt-out rate for generic levothyroxine was 22.1% after the intervention, compared with less than 2% of other drugs; indicating the continued lack of confidence in generic levothyroxine among many physicians (23).…”
Section: Therapeutic Equivalence Of Levothyroxine Tabletsmentioning
confidence: 99%